Age-related metabolite profiles and their relation to clinical outcomes in young adults, middle-aged individuals, and older people - Giesbertz, Pieter; Brandl, Beate; Volkert, Dorothee; Hauner, Hans; Skurk, Thomas (The FASEB Journal, 2023)
Age is a significant risk factor for common noncommunicable diseases, yet the physiological alterations of aging are poorly understood. We were interested in metabolic patterns between cross-sectional cohorts of different age ranges with particular emphasis on waist circumference. We recruited three cohorts of healthy subjects with different age ranges (adolescents 18-25 years, adults 40-65 years, and older citizens 75-85 years) and stratified these based on waist circumference. Using targeted LC-MS/MS metabolite profiling, we analyzed 112 analytes in plasma (amino acids, acylcarnitines, and derivatives). We associated age-related alterations with various anthropometric and functional parameters such as insulin sensitivity and handgrip strength. Strongest age-dependent increases were found for fatty acid-derived acylcarnitines. Amino acid-derived acylcarnitines displayed increased associations with BMI and adiposity. Some essential amino acids changed in opposite directions, being lower at increased age and higher with increasing adiposity. t-methylhistidine was elevated in older subjects, especially on an adiposity background, suggesting an increased protein turnover. Both aging and adiposity are associated with impaired insulin sensitivity. Skeletal muscle mass decreased with age and increased with adiposity. Profound differences in the metabolite signatures during healthy aging and elevated waist circumference/body weight were found. Opposite changes in skeletal muscle mass as well as possible differences in insulin signaling (relative insulin deficiency in older subjects versus hyperinsulinemia associated with adiposity), might be underlying origins for the observed metabolite signatures. We describe novel associations between metabolites and anthropometric factors during aging which underlines the complex interplay of aging, insulin resistance, and metabolic health.
CRIS-Team WoS Importer:2023-05-26